Assessment of ica A and D Genes in Biofilm producers methicillin-resistant Staphylococcus aureus isolates - Abdrabaa, Mariam Khamees; Aburesha, Rasmiya Abd (Iraqi Journal of Science, 2023)
This study investigates in vitro biofilm production. Presence of ica A and D genes in methicillin-resistant Staphylococcus aureus was evaluated for biofilm production by the microtiter plate method. Between December 2020 and October 2021, out of 215 clinical specimens were collected from patients with pulmonary fibrosis, pneumonia, bacteremia, chronic burns, deep wounds, urinary tract infection and catheterized patients. Out of which 45 MRSA isolates were identified by the susceptibility test utilizing cefoxitin and the occurrence of mecA gene for resistance for this antibiotic verified by polymerase chain reaction technique. A sensitivity test was conducted for five other antibiotics. All MRSA isolates were producers of biofilms but the formation of robust biofilms by 42% of MRSA isolates, 20% of isolates was intermediate and 38% of isolates weak. Formerly ica A and D genes, responsible for polysaccharide intracellular adhesin dependent biofilm formation were investigated in all MRSA isolates using the polymerase chain reaction technique. ica A were detect in 33 (73.3%) of the isolates and was lacking in 12 (26.6%) of the isolates. ica D gene was present in 38 (84.4%) isolates and was lacking in 7 (15.5%). However, the total number of isolates that contained icaA and D genes was 10 (22.2%). The most noteworthy finding was that the five weak isolates lacked any genes. Thus indicating that these isolates are capable of producing biofilm without the need for ica in order to make polysaccharide intracellular adhesin that means the isolates have an ability to form biofilm in ica independent biofilm mechanisms.